2009
DOI: 10.1021/np900334k
|View full text |Cite
|
Sign up to set email alerts
|

Biologically Active Tetranorditerpenoids from the Fungus Sclerotinia homoeocarpa Causal Agent of Dollar Spot in Turfgrass

Abstract: Nine new tetranorditerpenoid dilactones (2-10), together with two previously reported norditerpenoids dilactones (1, 11), and two known putative biosynthetic intermediates oidiolactone-E (12) and 13 were isolated from an ethyl acetate extract of a culture medium of Sclerotinia homoeocarpa. Structures and absolute configuration of these compounds were determined by spectroscopic methods and confirmed by X-ray crystallographic analysis of representative compounds. Compounds were evaluated for herbicidal, antipla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 34 publications
2
22
1
1
Order By: Relevance
“…Early studies noted root browning and cell death through the production of diffusible toxins [12] . Recent studies have identified several tetranorditerpenoid compounds that could be responsible for the root-browning and exhibit extremely phytotoxic properties; however, a correlation between the production of these compounds and disease symptoms was not established [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Early studies noted root browning and cell death through the production of diffusible toxins [12] . Recent studies have identified several tetranorditerpenoid compounds that could be responsible for the root-browning and exhibit extremely phytotoxic properties; however, a correlation between the production of these compounds and disease symptoms was not established [13] .…”
Section: Introductionmentioning
confidence: 99%
“…The application of chemical agents is a common method to avoid biotic-stress-induced damage in turfgrass. For instance, dollar spot disease in turfgrass is caused by the fungus Clarireedia homoeocarpa, and it could be suppressed by fungicide in creeping bentgrass [199][200][201][202]. Captan and Chlorothalonil are efficient fungicides against Curvularia trifolii, which causes foliar yellowing of Paspalum vaginatum [5,194].…”
Section: Biotic Stressmentioning
confidence: 99%
“…192 Examination of the endophytic A. wentii EN-48 (brown alga Sargassum sp., source unspecied) revealed three new tetranorlabdane diterpenoids asperolide A-C 203-205 193 in addition to the terrestrial fungal metabolites, wentilactones A and B, 194 LL-Z1271-b, 195 and a known tetranorditerpenoid derivative. 196 All of these known metabolites were rst time marine isolates. 193 Application of OSMAC (one strain-many compounds) methodology to Asteromyces cruciatus (unidentied decaying green alga, La Jolla, USA) identied the pentapeptide lajollamide A 206 (absolute conguration determined by total synthesis).…”
Section: Marine-sourced Fungi (Excluding From Mangroves)mentioning
confidence: 99%